Professores dos anos iniciais do ensino fundamental, pedagogia histórico-crítica e ensino de ciências: investigando articulações - Santos, Fábio Schwarz Soares dos [UNESP] (2015)
This study aimed to analyze the knowledge of a teachers group on Historical Critical Pedagogy (HCP) and its joints with the science teaching in the initial grades. Therefore, it was designed and developed a continuing education course for teachers of a municipal school from Bauru. The data were collected from material produced by the participants, observations of meetings, questionnaires and interviews, which are examined through Content Analysis. The data were organized into four themes: (In) formation sources, Critical Theories and HCP, Knowledge of HCP and HCP Science and Education. For the data analysis, it appears that the knowledge of teachers is limited, especially with regard to the bases from and to the HCP and the Science education is poorly articuled in this perspective. The teachers demonstrate that kwnow some principles of the theory and they indicate the need for theoretical study. We have discussed the need to theoretical domain of this theory by teachers and training as way for this process